Analysis of endogenous aldehydes in human urine by static headspace gas chromatography–mass spectrometry - Serrano, María; Gallego, Mercedes; Silva, Manuel (Journal of Chromatography A, 2016)
•HS–GC–MS method to determine 12 relevant endogenous aldehydes in human urine.•Simple, automatic and environmentally friendly method.•LODs (ng/L) at least one order of magnitude lower than those of recent alternatives.•Aldehydes are detected with good accuracy in un-diluted real urine samples.•Urine is a suitable matrix for monitoring aldehydes as markers of oxidative stress. Endogenous aldehydes (EAs) generated during oxidative stress and cell processes are associated with many pathogenic and toxicogenic processes. The aim of this research was to develop a solvent-free and automated analytical method for the determination of EAs in human urine using a static headspace generator sampler coupled with gas chromatography–mass spectrometry (HS–GC–MS). Twelve significant EAs used as markers of different biochemical and physiological processes, namely short- and medium-chain alkanals, α,β-unsaturated aldehydes and dicarbonyl aldehydes have been selected as target analytes. Human urine samples (no dilution is required) were derivatized with O-2,3,4,5,6-pentafluorobenzylhydroxylamine in alkaline medium (hydrogen carbonate–carbonate buffer, pH 10.3). The HS–GC–MS method developed renders an efficient tool for the sensitive and precise determination of EAs in human urine with limits of detection from 1 to 15ng/L and relative standard deviations, (RSDs) from 6.0 to 7.9%. Average recoveries by enriching urine samples ranged between 92 and 95%. Aldehydes were readily determined at 0.005–50μg/L levels in human urine from healthy subjects, smokers and diabetic adults.